THE EFFECTS OF EMOTIONAL AND FACTUAL MESSAGE FRAMING ON PUBLIC ATTITUDES TOWARD WOLF REINTRODUCTION IN COLORADO - Petr, Anna, author; Anderson, Ashley A., advisor; Tham, Samuel M., advisor; Mao, KuoRay, committee member; Sivakumar, Gayathri, committee member (Colorado State University. Libraries, 2026)
Gray wolf reintroduction in Colorado is a highly visible and often emotional conservation issue, and the way messages about wolves are framed has significant influence on how the public responds. This study examined how emotional and factual message frames shape attitudes toward wolf reintroduction and how audience involvement, specifically motivation and prior knowledge, guided the route through which people process these messages. Using the Elaboration Likelihood Model as a framework, this study employed a between-subjects experimental survey in which participants viewed a short emotional or factual video designed to resemble social media content about wolf reintroduction. The emotional frame emphasized affective cues and empathy, while the factual frame focused on ecological information and argument strength. After viewing the stimulus, participants responded to measures of attitudes, affective response, and message credibility. Results indicated that factual framing significantly increased perceived informational strength compared to emotional framing. However, emotional framing did not produce significantly greater affective responses, and the interaction between message framing and audience involvement was not supported. Mediation analyses revealed that message credibility significantly predicted attitude change, although the direct effect of framing on attitudes was not significant. Most notably, perceived message credibility emerged as a key pathway through which framing influenced attitude change, suggesting that how credible a message appears to audiences may matter more than its emotional or factual orientation alone. This study contributes to conservation communication by highlighting the role of message credibility and audience characteristics in wildlife-related persuasion, with practical implications for agencies seeking to build trust and design effective outreach strategies.
Keywords: Credibility; Human-wildlife conflict; Wolf reintroduction; Elaboration likelihood model; Conservation communication; Wildlife conservation